2021
DOI: 10.1186/s12859-020-03941-4
|View full text |Cite
|
Sign up to set email alerts
|

Boolean implication analysis unveils candidate universal relationships in microbiome data

Abstract: Background Microbiomes consist of bacteria, viruses, and other microorganisms, and are responsible for many different functions in both organisms and the environment. Past analyses of microbiomes focused on using correlation to determine linear relationships between microbes and diseases. Weak correlations due to nonlinearity between microbe pairs may cause researchers to overlook critical components of the data. With the abundance of available microbiome, we need a method that comprehensively … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Due to their importance and universality, BARs have been analyzed in many recent research efforts [6][7][8][9]. As just one example, [10] combined the use of a StepMiner algorithm and a sparsity test to find statistically-significant BARs, which can be generalized to find three-way-instead of merely pairwise-BARs as a way to reduce the computational burden and involve more general interactions between genes [11].…”
Section: Prior Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to their importance and universality, BARs have been analyzed in many recent research efforts [6][7][8][9]. As just one example, [10] combined the use of a StepMiner algorithm and a sparsity test to find statistically-significant BARs, which can be generalized to find three-way-instead of merely pairwise-BARs as a way to reduce the computational burden and involve more general interactions between genes [11].…”
Section: Prior Workmentioning
confidence: 99%
“…Along similar lines, significant BARs have been found associated with celldifferentiation, cellular-development and tissue-function [9], [34]–[37]. More recent work has shown that, while many BARs differentiate between different cell-types in the micro-biome, there are also many BARs that are strongly conserved across microorganisms, potentially highlighting ‘universal’ gene-functions important for survival [6].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Our methods have not previously been applied to stem cell-derived retinal cell types, but have yielded insights into changes in transcriptional profiles of healthy retina and retinoblastoma [74]. The StepMiner and BooleanNet algorithms were developed for microarray data by Sahoo et al to identify Boolean implication relationships between genes, but have since been applied to a wide variety of high-throughput data, such as RNA-seq, scRNA-seq and microbiome data [68,[75][76][77].…”
Section: A Boolean Approachmentioning
confidence: 99%